Some Scottish novelists - Fox, Martha (My University, 1897)
Introduction: Scotland the size and population being taken into consideration, stands near the first if not at the head in literary ranks. With other countries it has followed the usual line of development with one exception, that of the drama. The ballad literature is exceptionally fine, in fact is considered, by some critics, the best of the kind ever written. Their lyrical poetry contains some of the most beautiful songs ever produced. Their history and essay work is not so conspicuously good as their work in other lines, but still in this we must make our exception, that of Carlyle. To the present ruling is due the honor of producing the best of Scottish writing the novel. Almost all types of the novel are here represented. It would be impossible in this small space to speak of all the Scotch novelists so I will confine myself to six of the most famous of them and give a few thoughts on their preparation and work, not so much from my own ideas as from those of others who are more competent to judge than I.
Citation: Fox, Martha. Some Scottish novelists. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Novels; Literature; Scotland; Sir Walter Scott; George Macdonald; Robert Louis Stevenson; J. M. Barrie; S.R. Crockett; John Watson; Ian Maclaren; Theses; Manuscripts (documents)